Mechanical Analysis of a 3-DOF Under-constrained Parallel Robot with Variable Cable Mast Heights - Zhao Tao; Zheng Yi; Ding Xiaojun; Li Keqiang; Yang Jubiao; Zhu Yang (Jixie chuandong)
The cable-driven parallel robot is a special flexible mechanism in parallel mechanism, the end-effector of which is driven by cables instead of rigid rods. It integrates the advantages of flexible robots and parallel robots. A three-degree-of-freedom (3-DOF) under-constrained parallel robot with variable cable mast heights is investigated in this study. The inverse kinematics model of the robot is established by using the vector closed-loop principle. The forward kinematics model of the robot is derived according to cable lengths. The dynamics model of the robot is established based on the Lagrange formula. The static equilibrium workspace (SEW) of the robot is studied using the Monte-Carlo method. Given the motion trajectory of the end-effector, the expected three cable lengths are obtained through the inverse kinematics model of the robot. Taking the expected three cable lengths as the experimental input, the experimental curves of cable lengths and cable tensions as well as the forward kinematics trajectory of the robot are obtained. The experimental results validate the correctness of the forward and inverse kinematics models and the dynamics model of the robot, as well as the effectiveness of the SEW.